Neuroadaptive User Experience Framework for Human–AI Teaming in Defense Industry - Wachnata, Dascha Abhista; Jandhana, IB Putra; Aritonang, Sovian (Indonesian Journal of Advanced Research, 2025)
Modern defense operations require resilient human–AI teaming under cognitive stress, yet static systems often fail to adapt, reducing trust and mission effectiveness. A Systematic Literature Review (2016–2025) across human factors, neuroergonomics, and defense HCI was conducted to conceptualize a Neuroadaptive User Experience (NUX) framework. Findings show that multimodal neurophysiological sensing (EEG, heart rate variability, eye tracking) can detect workload fluctuations, while adaptive interventions—task redistribution, interface simplification, and timing adjustments—sustain performance and accelerate recovery. The NUX framework integrates state sensing, interpretation, adaptive automation, and transparent feedback. Despite challenges in sensor reliability, calibration, and ethical governance, NUX represents a paradigm shift toward human-centered defense systems that enhance resilience, trust, and mission outcomes.